Supercapacitors: Highly Stable Transparent Conductive Silver Grid/PEDOT:PSS Electrodes for Integrated Bifunctional Flexible Electrochromic Supercapacitors (Adv. Energy Mater. 4/2016). Issue 4 (February 2016) - Cai, Guofa; Darmawan, Peter; Cui, Mengqi; Wang, Jiangxin; Chen, Jingwei; Magdassi, Shlomo; Lee, Pooi See
Abstract : A novel electrochromo‐supercapacitor based on a stable hybrid transparent conductive electrode is demonstrated by Pooi See Lee and co‐workers in article number 1501882. The bifunctional device performs as a regular energy storage device and simultaneously monitors the level of stored energy with a rapid and reversible color variation, even in high current charge/discharge conditions.